2018
DOI: 10.1021/acs.biochem.8b00403
|View full text |Cite
|
Sign up to set email alerts
|

The Retinitis Pigmentosa-Linked Mutations in Transmembrane Helix 5 of Rhodopsin Disrupt Cellular Trafficking Regardless of Oligomerization State

Abstract: G protein-coupled receptors can exist as dimers and higher-order oligomers in biological membranes. The specific oligomeric assembly of these receptors is believed to play a major role in their function, and the disruption of native oligomers has been implicated in specific human pathologies. Computational predictions and biochemical analyses suggest that two molecules of rhodopsin (Rho) associate through the interactions involving its fifth transmembrane helix (TM5). Interestingly, there are several pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 66 publications
(164 reference statements)
6
34
0
Order By: Relevance
“…Based on the measured reduction of the outer segment diameter and the corresponding reduction in the disc surface area in F220C mice, we estimate that the amount of rhodopsin transported to the outer segment is approximately 92% of WT. This explanation is consistent with a recent finding that the F220C rhodopsin mutant has a minor trafficking defect in cultured mammalian cells, with only 86% of mutant protein trafficked to the plasma membrane 9 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the measured reduction of the outer segment diameter and the corresponding reduction in the disc surface area in F220C mice, we estimate that the amount of rhodopsin transported to the outer segment is approximately 92% of WT. This explanation is consistent with a recent finding that the F220C rhodopsin mutant has a minor trafficking defect in cultured mammalian cells, with only 86% of mutant protein trafficked to the plasma membrane 9 .…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the only study to address the effect of disrupted rhodopsin dimerization in intact photoreceptors reported that inhibitory peptides 46 , shown to mildly disrupt rhodopsin dimerization in vitro 47 , caused rhodopsin mislocalization 46 . Yet, another recent study in mammalian cells suggested that F220C mutant rhodopsin does not affect its dimerization 9 . While rhodopsin dimerization within disc membranes has been shown through atomic-force microscopy 48 and cryo-electron microscopy 49 , there is currently no assay for analyzing rhodopsin dimerization during folding and trafficking, precluding us for identifying whether the F220C mutation in rhodopsin does indeed affect its dimerization in vivo, and, subsequently, what the role of rhodopsin dimerization in intact photoreceptors is.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Substitutions that affect rhodopsin kinetics are known to have evolved convergently in distantly related species inhabiting dim-light environments [46,47], including other fishes inhabiting the same rivers of the Amazon basin [37]. Interestingly, mutagenesis studies in bovine rhodopsin have also shown that the F220C substitution experimentally decreases the rate of retinal release [35]. Although the link between these shifts in rhodopsin kinetics and effects on visual physiology remains to be investigated, our results suggest that shifts in important aspects of rhodopsin function are coincident with the evolution of electrosensory systems in gymnotiforms.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-II active-state structure of rhodopsin [33], the side chain of site 258 is closer to the phenylalanine at site 220 than any other residue in rhodopsin (figure 2a). The F220C mutation has been shown to impair both rhodopsin dimerization [34] and its kinetic properties [35]. These structural differences in helices 5 and 6, critical domains for rhodopsin dimerization and activation [20], might act to mitigate, or even mask the pathogenic effect of the substitutions at site 220.…”
Section: (C) Structural Differences Mask the Effects Of A Visual Disementioning
confidence: 99%